2005
DOI: 10.1289/ehp.7475
|View full text |Cite
|
Sign up to set email alerts
|

Bone as a Possible Target of Chemical Toxicity of Natural Uranium in Drinking Water

Abstract: Uranium accumulates in bone, affects bone metabolism in laboratory animals, and when ingested in drinking water increases urinary excretion of calcium and phosphate, important components in the bone structure. However, little is known about bone effects of ingested natural uranium in humans. We studied 146 men and 142 women 26–83 years of age who for an average of 13 years had used drinking water originating from wells drilled in bedrock, in areas with naturally high uranium content. Biochemical indicators of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(126 citation statements)
references
References 17 publications
3
121
0
2
Order By: Relevance
“…A cohort study was done in Finland on people having uranium contaminated water from drilled wells. It was found that uranium can accumulate in the bones and kidneys [79].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort study was done in Finland on people having uranium contaminated water from drilled wells. It was found that uranium can accumulate in the bones and kidneys [79].…”
Section: Discussionmentioning
confidence: 99%
“…A paper has mentioned many studies related to reproductive toxicity in humans and animals from uranium or depleted uranium exposure [93]. There are risks associated with long-term exposure from dusty particles of depleted uranium, and its drinking water contamination can lead to damaged lungs, kidneys, and brain [63,79,88,89,[94][95][96][97][98][99]. This study reported that 92% of radiation-exposed dwellers were not taking ionizing radiation-free drinking water.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical toxicity effects on the human kidney by chronic ingestion of uranium through drinking water in the range of 0.004 to 9 µg.L -1 per body weight per day may produce interference with kidney functions (Zamora et al, 1998). In a more recent study on humans by Kurttio et al (2005), nephrotoxic effects of uranium in drinking water were found even for low concentrations -without a clear threshold. Most results from uranium studies in drinking water suggest that the safe concentration of uranium in drinking water may be within the range of proposed guideline values of 2-30 µg.L -1 (Kurttio et al, 2002;WHO, 2008).…”
Section: Risk From the Intake Of Uranium Through Ingestionmentioning
confidence: 98%
“…Biomarkers of lung cancer and other lung damage were proposed, since dust inhalation is the primary route of occupational exposure to uranium and results from experimental (Leach et al 1973, Mitchel et al 1999 and epidemiological (Ritz 1999, Guseva Canu et al 2011 studies suggest this is potentially a key issue. Biomarkers of renal and bone damage were also proposed, because uranium accumulates in these organs and tissues and evidence from animal and epidemiological studies indicates uranium related effects in kidney (Prat et al 2011, Gueguen and Rouas 2012, McDiarmid et al 2013 and bone (Kurttio et al 2005). Biomarkers of lympho-hematopoietic system impairment were proposed, because of possible irradiation of pulmonary macrophages, lymph nodes and bones (Guseva Canu et al 2011).…”
Section: Proposed Biomarkersmentioning
confidence: 99%